Building a Personalized Cancer Treatment System - Martínez Porras, Alexandra (2016)
This paper reports the process by which a personalized cancer treatment system was built, following a user-centered approach. We give some background on personalized cancer treatment, the particular tumor chemosensitivity assay supported by the system, as well as some quality and legal issues related to such health systems. We describe how Contextual Design was applied when building the system. Contextual design is a user-centered design technique involving seven steps. We also provide some details about the system implementation. Finally, we explain how the Think-Aloud protocol and Heuristic Evaluation methods were used to evaluate the system and report its results. A qualitative assessment from the users perspective is also provided. Results from the heuristic evaluation indicate that only one of ten heuristics was missing from the system, while five were partially covered and four were fully covered.